Determination of some trace heavy Metals (Pb, Cd, Cu) in sediments of the Euphrates River (Deir Ezzor Governorate) - العلي لحاظ; إبراهيم نيصافي; حسام الدين لايقه; محمد حسن (Latakia University Journal -Biological Sciences Series, 2024)
This study aimed to determine the level of pollution with some heavy elements (Pb, Cd & Cu) in the sediments of the Euphrates River within Deir Ezzor Governorate, in addition to studying the temporal and spatial changes of the distribution of some heavy metal elements studied in the river environment. Three sampling stations have been identified downstream within Deir Ezzor governorate: Hatla, Hawija Sakr and Rushdia. Water and sediment samples were collected quarterly during 2021-2022 and heavy metal element concentrations were determined using atomic absorption technology. The three measured heavy metal elements showed a great convergence in their values between the study stations and showed that there were no significant differences between them (P > 0.05), where the results showed that the concentrations of the studied elements in the sediments can be counted from the environmental evidence of pollution of the aquatic environment. The results showed clear seasonal changes in the concentrations of the studied elements, where their values increased in the summer and spring compared to the winter and autumn seasons, in addition to differences between stations.